FARKAS-TYPE RESULTS FOR NONCONVEX SYSTEMS INVOLVING COMPOSITE FUNCTIONS WITH APPLICATIONS - Nguyễn Định; Trần Hồng Mơ (Tạp chí Khoa học Đại học Đà Lạt)
A new kind of closedness conditions (CC) is introduced. Several Farkas-type results and their characterisations for nonconvex systems involving DC and composite functions are established under/via this condition. As applications, the results are applied to get optimality conditions, duality results for classes of DC/convex problems.